Education on the Importance of Literacy and a Reading Culture for Golden Indonesia 2045 for MTS Asy-Syifa Students : Edukasi Pentingnya Literasi dan Budaya Membaca untuk Indonesia Emas 2045 terhadap Siswa MTS Asy-Syifa - Sakina, Rahma; Mareta, Finka (CONSEN: Indonesian Journal of Community Services and Engagement, 2025)
The Indonesian government has declared a vision for a Golden Indonesia by the year 2045. To create a bright future for Indonesia in the next 20 years, we must cultivate an outstanding young generation today by raising awareness of the importance of literacy and a reading culture among the youth. Literacy is not merely the technical ability to read and write, but goes beyond that—it includes the ability to understand, interpret, evaluate, and use information in order to participate actively in society. Once this awareness and mindset are formed, it is hoped that Indonesia's young generation will develop more productive habits by reading more books, thereby broadening their horizons, fostering a love for knowledge, cultivating curiosity, and developing critical thinking skills. This will help them become independent learners capable of responding to the increasingly complex challenges of the times. This community service activity employed a participatory action research method and was conducted with students of Madrasah Tsanawiyyah As-Syifa in West Bandung Regency. The activity took place on May 15, 2025. The students’ pre-test results showed an average score of 66.27. This finding indicates that the students had not yet fully understood the meaning of literacy or the importance of literacy and a reading culture. After being provided with education on the importance of literacy and reading habits, a post-test was administered. The results showed an increased average score of 83.09 and a calculated N-gain of 0.51, which falls into the medium category. These results indicate that students' understanding and awareness of the importance of literacy and a reading culture had improved.